Low indoleamine 2, 3‐dioxygenase activity in persistent food allergy in children. Issue 2 (26th November 2015) - Buyuktiryaki, B.; Sahiner, U. M.; Girgin, G.; Birben, E.; Soyer, O. U.; Cavkaytar, O.; Cetin, C.; Arik Yilmaz, E.; Yavuz, S. T.; Kalayci, O.; Baydar, T.; Sackesen, C.
Abstract: Background: Indoleamine 2, 3‐dioxygenase (IDO), which degrades tryptophan (Trp) to kynurenine (Kyn), has been demonstrated to contribute to modulation of allergic responses. However, the role of IDO in food allergy has not yet been elucidated. Methods: Serum Trp and Kyn concentrations were analyzed by high‐pressure liquid chromatography. Expression of IDO gene was measured by real‐time PCR. The levels of interleukin (IL)‐4, IL‐10, and interferon (IFN)‐γ in cell culture supernatants were measured by ELISA. Results: Kyn/Trp (IDO activity) was significantly lower in subjects with food allergy ( n = 100) than in aged‐matched healthy controls ( n = 112) ( P = 0.004). Kyn/Trp was decreased from healthy through completely tolerant, partially tolerant, and reactive ones [LN transformation (mean ± SEM) healthy: 3.9 ± 0.02 μM/mM; completely tolerant: 3.83 ± 0.04; partially tolerant: 3.8 ± 0.06; reactive: 3.7 ± 0.04] ( P = 0.008). The frequency of genetic polymorphisms of IDO did not reveal a significant association with Trp, Kyn, and Kyn/Trp in healthy and food‐allergic cases. Culture of PBMC experiments yielded that IDO mRNA expression was not different between tolerant and reactive groups. IL‐4 synthesis when stimulated with casein increased significantly in subjects who are reactive and tolerant to foods ( P = 0.042, P = 0.006, respectively). Increase in IL‐10 synthesis was observed only in children tolerant to milk, but not in reactive ones. IFN‐γ synthesis, when stimulated with IL‐2 and β‐lactoglobulin in cell culture, was significantly higher in subjects tolerant to milk than in the reactive ones ( P = 0.005 and P = 0.029, respectively). Conclusion: Our results imply the probability of involvement of IDO in development of tolerance process, and we presume that high IDO activity is associated with nonresponsiveness to food allergens despite allergen sensitization.